2014
DOI: 10.1186/1471-244x-14-87
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of attitudes about suicide among psychiatrists in Shanghai

Abstract: BackgroundAttitudes and knowledge about suicide may influence psychiatrists’ management of suicidal patients but there has been little research about this issue in China.MethodsWe used the Scale of Public Attitudes about Suicide (SPAS) – a 47-item scale developed and validated in China – to assess knowledge about suicide and seven specific attitudes about suicide in a sample of 187 psychiatrists from six psychiatric hospitals in Shanghai. The results were compared to those of 548 urban community members (asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…This scale was built up of three parts. 28 Part A is composed of 73 statements about attitudes toward suicide. Part B includes 12 statements about 12 difficult scenarios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale was built up of three parts. 28 Part A is composed of 73 statements about attitudes toward suicide. Part B includes 12 statements about 12 difficult scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…This instrument is intended to measure attitudes of the respondents toward suicide committed by strangers, loved ones, and social groups under certain circumstances. 28 , 33 The scale is proposed to be applicable across communities in comparative studies of attitudes toward suicide.…”
Section: Resultsmentioning
confidence: 99%
“…Existing evidence suggests that suicide and self-harm related attitudes span issues concerning morality of suicide, positive/negative views about suicidal patients or persons who die by suicide, and beliefs about the clinician's own ability to help patients experiencing suicide and self-harm (e.g., Batterham et al, 2013;Botega et al 2005Botega et al , 2007. Researchers have found that behavioral health professionals' attitudes about self-harm and suicide may influence their willingness and ability to identify, assess, and treat high-risk patients (Jiao et al, 2014;Long, Manktelow, & Tracey, 2013). Thus, changing negative attitudes among providers who are likely to encounter individuals at increased risk for suiciderelated behavior suggests a promising intervention point.…”
Section: Behavioral Health Provider Suicide Prevention Contacts Compmentioning
confidence: 99%
“…They found that although physicians considered suicide as a preventable worldwide public health social issue, they had stigmatized views about the suicidal patient and comprehended such patient less with lower sympathy. Even after filtering sociodemographic characteristics, the analysis remained significant [27].…”
Section: Introductionmentioning
confidence: 97%